The Influence of Work Environment and Internal Control on Employee Performance: A Study at Breaktime Reflexology in Palu City - Moh Zuljalali Wal Irsyam; Ernawaty Usman; Rahayu Indriasari; Latifah Sukmawati Yuniar (Yayasan Amerta Insan Unggul, 2026)
This study aims to examine and analyze the influence of the work environment and internal control on employee performance at Breaktime Reflexology in Palu City. Using a quantitative approach, data were collected through questionnaires and interviews from all 65 employees, applying a saturated sampling technique. The analytical method used was multiple linear regression with the aid of SPSS version 25. The results showed that the work environment and internal control simultaneously have a positive and significant effect on employee performance. Partially, both variables also have a positive and significant influence. These findings indicate that improvements in the physical and non-physical aspects of the work environment—such as cleanliness, comfort, and harmonious relationships—enhance employee motivation, job satisfaction, and productivity. Moreover, effective implementation of internal control mechanisms, including clear division of duties, supervision, and compliance procedures, fosters accountability, discipline, and organizational trust. The study supports Stewardship Theory, emphasizing that employees, when provided with a supportive environment and structured control system, are motivated to act in the organization’s best interest. This research contributes empirically to human resource management practices in service-based industries, particularly reflexology centers, by highlighting that organizational success depends on the synergy between conducive work conditions and robust internal controls. Future studies may include other performance determinants such as leadership, motivation, and organizational culture.